Development of a multi rotor floating offshore system based on vertical axis wind turbines. Issue 1 (1st April 2022) - Jamieson, P; Simao Ferreira, C; Dalhoff, P; Störtenbecker, S; Collu, M; Salo, E; McMillan, D; McMorland, J; Morgan, L; Buck, A
Abstract: The upscaling of wind turbines results in fewer units per installed MW reducing infrastructure and maintenance costs of offshore wind farms. Multi rotor systems (MRS), comprising many wind turbine rotors on a single support structure, are potentially a means to maximize the upscaling benefit in achieving larger unit capacities than is feasible or economic with the conventional, 3-bladed horizontal axis wind turbine (HAWT). The MRS has an inherent upscaling advantage which, for a system with many rotors compared to a single rotor, reduces the total weight and cost of rotor-nacelle assemblies by a large factor. An innovative MRS design is presented based on vertical axis wind turbine (VAWT) rotors of the 2-bladed, H-type. Many disadvantages of VAWT design compared to HAWT in a single rotor system (reduced power performance and higher drive train torque, for example) are resolved in the MRS configuration. In addition, reduced component number and simpler components is advantageous for reliability and O&M cost. This MRS concept has many synergies arising from the choice of VAWT rotors. Results comprise a high-level evaluation of system characteristics and the first stage of more detailed investigation of aerodynamics of the high aspect ratio VAWT.